The Combined Method of Forecasting the Investments within the Framework of Panel Data Models - Babeshko, Lyudmila O.; Mikhaleva, Maria Y.; Orlova, Irina V. (Journal of Reviews on Global Economics, 2018)
The article is devoted to the panel data modeling of the firm’s investments depending on its market value and the size of fixed assets. The Grunfeld’s investment data as provided in R package were used as the initial data. The data frame contains annual observations for 11 firms over 20 years. The main econometric models for panel data (pooled model, fixed effects model, random effects model) were estimated. To make choice the most effective specification of the model the character of effects was tested. The heterogeneity of firms was explained by individual random factors. The comparative analysis of parameters’ estimates was performed using the basic panel data models and their optimal combination in the framework of combined assessment (forecasting). Weight coefficients of hybrid forecasts are assigned as directed by the combined model list in accordance with standard optimality requirements. It was shown that the results of the combined assessment coincided with the estimates of the random effects model.